Shared and divergent principles of synaptic transmission between cortical excitatory neurons in rodent and human brain - de Kock, Christiaan P. J.; Feldmeyer, Dirk (Frontiers in Synaptic Neuroscience, 2023)
Information transfer between principal neurons in neocortex occurs through (glutamatergic) synaptic transmission. In this focussed review, we provide a detailed overview on the strength of synaptic neurotransmission between pairs of excitatory neurons in human and laboratory animals with a specific focus on synaptic data obtained using patch clamp electrophysiology. We reach two major conclusions: 1) the synaptic strength, measured as unitary excitatory postsynaptic potential (or uEPSP), is remarkably consistent across species, cortical regions, layers and/or celltypes (median 0.5 mV, interquartile range 0.4 -1.0 mV) with most variability associated with the cell-type specific connection studied (min 0.1 -max 1.4 mV), 2) synaptic function cannot be generalized across human and rodent, which we exemplify by discussing the differences in anatomical and functional properties of pyramidal-to-pyramidal connections within human and rodent cortical layers 2 and 3.With only a handful of studies available on synaptic transmission in human, it is obvious that much remains unknown to date. Uncovering the shared and divergent principles of synaptic transmission across species however, will almost certainly be a pivotal step towards understanding human cognitive ability and brain function in health and disease.